Raising the level of technical-tactical actions in standing by including leg actions as subsidiary elements - Shakhmuradov, Y.; Podlivaev, B. (International Journal of Wrestling Science, 2011)
Considering the fact that the time for the fall was reduced to 1 sec, the importance of leg holds is considerably increased. The following points reinforce the need for leg holds: 1) In accordance with the rules the holds begun on the mat and completed off the mat are scored. That made the wrestlers study and perfect the Double Leg holds. To our mind, the holds with the legs action are efficient counter actions directed to breaking the attacks, that is, subsidiary wrestling elements with leg actions important means through which it is possible to create counter holds. 2) It is also mandated by the rules that wrestlers shall always be in constant contact, that is, in a conflict situation. As the intensity of the bout increased, the position time spent in the Double Body Lock was cut short as the time to preparation to any attack was also reduced. In these extreme situations subsidiary elements of leg wrestling can play a vital role in reaching victory. The results of a survey of leading coaches' opinions dealing with young wrestlers made it possible to define the basic elements of the holds with legs actions (simple through complex). The simple ones include: Leg Trips, Leg Sweeps, Leg Hooks, Leg Beats and the complicated elements cover Grapevines, Sweeps, and Leg Lifts. The urgency of this problem increased because the rules reward those wrestlers who apply high amplitude holds. Naturally, every wrestler is eager to get the highest evaluation. The efficiency of the holds with leg actions makes it possible to solve this task. At that, the reliability of applying the holds with the leg actions depends on the efficiency of applying the holds, namely variance and adaptability of the holds are defined by the possibility to modify the methods of their application. All the more reason for coaches to pay serious attention to the methods of training and perfection of these tactical holds with leg actions.